Flying witch. 2 - Ishizuka, Chihiro (Vertical Comics, 2017)
Makoto goes to a cherry blossom festival and runs into her sister, Akane. Then Akane drops by and teaches Makoto new tricks for flying and some easy spells. The girls' cousin, Chinatsu, sees their talents and makes a special request of them.